Strategies for increasing tax revenue in tourism sector - Djulius, Horas (Economic Journal of Emerging Markets, 2018)
This study examines taxpayer considerations to fulfill their obligations since law enforcement and tax administration improvement were not adequate to explain the gap between actual tax and its target. A survey was conducted to hotel, restaurant and tourist destination managers in Bandung since one-third of local taxes derived from the tourism sector. We use a probit model to clarify the influence of religious activities, trust in government institutions, public services, people’s pride, prodemocratic attitude, to taxpayer morality. The study concludes that taxpayers in the tourism sector have a higher local tax morality than central tax morality and only the public services which have a consistent and significant impact on both tax moralities. The local governments and central government can develop improved strategies to increase revenue from tourism sector by providing better public service, which directly or indirectly enhances the tourism sector performance.